2011
DOI: 10.1371/journal.pntd.0000951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urine CCA Assays for Detection of Schistosoma mansoni Infection in Western Kenya

Abstract: Although accurate assessment of the prevalence of Schistosoma mansoni is important for the design and evaluation of control programs, the most widely used tools for diagnosis are limited by suboptimal sensitivity, slow turn-around-time, or inability to distinguish current from former infections. Recently, two tests that detect circulating cathodic antigen (CCA) in urine of patients with schistosomiasis became commercially available. As part of a larger study on schistosomiasis prevalence in young children, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
154
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 32 publications
21
154
3
1
Order By: Relevance
“…The present study reports serological prevalence of human toxocariasis in children of East Azerbaijan Province .In different parts of the world, serological studies have demonstrated a variation in Toxocara seroprevalence ranging from 2.3% to 86% 11,14 . However the present study showed a higher rate of infection (29.46 %) than that of (6.4 %) subjects residing in a rural area near Chandigarh 11 , Slovak Republic 15 which may be due to low standards of hygiene, frequent contact with the contaminated soil and less paternal education 23,26,27 . In our study, higher prevalence of infection was found among males than females.…”
Section: Resultscontrasting
confidence: 53%
“…The present study reports serological prevalence of human toxocariasis in children of East Azerbaijan Province .In different parts of the world, serological studies have demonstrated a variation in Toxocara seroprevalence ranging from 2.3% to 86% 11,14 . However the present study showed a higher rate of infection (29.46 %) than that of (6.4 %) subjects residing in a rural area near Chandigarh 11 , Slovak Republic 15 which may be due to low standards of hygiene, frequent contact with the contaminated soil and less paternal education 23,26,27 . In our study, higher prevalence of infection was found among males than females.…”
Section: Resultscontrasting
confidence: 53%
“…Tests for antibodies to schistosomes were performed by enzyme-linked immunosorbent assay (ELISA) using soluble worm antigen preparation using previously described methods. 38 This test does not distinguish between Schistosoma spp.…”
Section: Methodsmentioning
confidence: 99%
“…20 A child with one or more positive stool slides or with positive SWAP ELISA results was considered infected with S. mansoni . Because Usoma has not been targeted by any preventive chemotherapy, positive serologic results were likely to represent true infections.…”
Section: Methodsmentioning
confidence: 99%
“…A fresh urine sample was also requested and was tested with a commercially available circulating cathodic antigen (CCA) assay (Rapid Medical Diagnostics, Pretoria, South Africa), which includes a standard curve that allows for a gross estimate of infection intensity. 20,21 Urine CCA was detected by carbon-conjugated antibody and measured as either negative or as 1-, 2-, or 3-plus. Among those children who tested positive for S. mansoni by stool and/or SWAP ELISA, infections were classified as low intensity (CCA negative or 1-plus), or high intensity (CCA 2-or 3-plus).…”
Section: Methodsmentioning
confidence: 99%